On Detour Distance Laplacian Energy (Journal of Informatics and Mathematical Sciences, 2017)
The Detour distance laplacian energy of a simple connected graph \(G\) is defined as the sum of the absolute values of the Eigen values of the detour distance laplacian matrix of \(G\). In this paper, the bounds for detour distance laplacian energy is obtain and also the detour distance laplacian energy of standard graphs and the Cartesian product of certain graphs with \(P_2\) are computed.
Keywords: Detour distance Laplacian matrix; Detour distance Laplacian Eigen value; Detour distance Laplacian energy